Implementing artificial intelligence (AI) in teaching english: A case study at SMP Muhammadiyah 1 Surakarta - Erna Yuliani; Muamaroh Muamaroh (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study investigates the implementation of Artificial Intelligence (AI) in teaching English at SMP Muhammadiyah 1 Surakarta. It employed a qualitative case study approach involving an English teacher, Mrs. FAM, who was selected based on her innovative contributions to AI adoption in English language instruction. Data were collected through semi-structured interviews, participant observation, and documentation. The interview was conducted in Indonesian to obtain richer and more detailed information, while classroom observation involved 32 students to examine the implementation of AI, student-teacher interaction, effectiveness, and possible barriers. The findings reveal that AI was mainly used as a supporting tool in lesson preparation, material development, instructional media, and evaluation. In practice, AI-assisted materials were not used directly, but were first reviewed and adapted to suit the curriculum and students’ needs. The implementation was reflected in the teaching of question tags and passive voice through the use of Google Sites, PowerPoint, projectors, and AI tools such as ChatGPT and Gemini. In addition, evaluation was conducted through individual exercises on Google Sites, allowing students to receive immediate scores. The study concludes that AI plays a complementary role in supporting more practical and organized English language teaching, although its effectiveness depends on the teacher’s pedagogical adaptation.